Pembuatan Data Pelanggan Menggunakan Aplikasi Edobi Pada UMKM “Jojo Laundry” - Yosefina, Novi; Octaviani, Octaviani; Tobing, Yopetrus; Monica, Santa; Marbun, Zipora; Sitompul, Grace Orlyn (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This research aims to support Jojo Laundry, a micro, small, and medium enterprise (MSME) located in Parongpong, West Java, in transitioning to digital systems by implementing the Edobi application for recording customer data and transactions. The implementation process involved several stages, including interviews with the business owner, training sessions on how to use the application, inputting customer data, and evaluating the system’s effectiveness. The findings indicate that the use of Edobi significantly improves the efficiency of daily transaction recording and customer management. Information becomes more organized, easily accessible, and protected from the risk of data loss. Although the business owner needs time to fully adapt to the new technology, the initial impact has been positive. Digitalisation is expected to contribute to the long-term growth and competitiveness of Jojo Laundry. It is recommended to provide ongoing assistance and expand digital education to other MSMEs through seminars or workshops.